Antioxidant Properties of Selenophene, Thiophene and Their Aminocarbonitrile Derivatives - Tavadyan, Levon A. (Antioxidants (Basel), 2017)
The oxygen radical absorbance capacity (ORAC) method was used to detect the antiperoxyradical ability of organoselenium compounds: selenophene and its derivative, 2-amino-4,5,6,7-tetrahydro-1-selenophene-3-carbonitrile (ATSe); while as a comparison, the sulfur-containing analogue of selenophene—thiophene and its derivative—2-amino-4,5,6,7-tetrahydro-1-thiophene-3-carbonitrile (ATS)—was selected. Cyclic voltammetry (CV), differential pulse voltammetry (DPV) and squarewave voltammetry (SWV) methods were used to determine the redox characteristics of organoselenium and organosulfur compounds. The antiradical activity and capacity of the studied compounds were also measured by using stable radical 2,2ʹ-diphenyl-1-picrylhydrazyl (DPPH). Detected anodic peaks of the oxidation of selenophene, thiophene and their derivatives in CV, DPV and SWV in the interval of −1200 ÷ (+1600) mV potentials in regard to the Ag/Ag(+) medium of acetonitrile prove the presence of antiperoxyradical activity in regard to oxidizers, i.e., peroxyradicals. The chemical mechanism of the antiperoxyradical ability of selenophene, thiophene and their organic derivatives is proposed.